Educational Institutions and the State in Medieval Islam: The Fatimid of Egypt as a Case Study - Souad, Merah; Ramdane, Tahraoui (2017)
This presentation will discuss the role of the different educational institutions and their relationship with the state through the case study of the Fatimids of Egypt